THE EFFECT OF SERVICE QUALITY, DISCONFIRMATION, CUSTOMER SATISFACTION ON CUSTOMER LOYALTY ON NAAVAGREEN BEAUTY CLINIC SERVICES IN YOGYAKARTA - Flavianus Yoga Tridandy Chandra; Ida Bagus Nyoman Udayana; Putri Dwi Cahyani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study is a quantitative study using survey methods so that the population in the study are customers who use the services of the NAAVAGREEN beauty clinic in Yogyakarta. In taking the sample using purposive sampling technique. Data collection uses a questionnaire method that has been tested for validity and reliability. This study uses a sampling technique by distributing questionnaires to take a sample of 100 people so that they can be tested for validity and reliability. The results showed that there was a positive effect of product quality on the decision to repurchase beauty products for Naavagreen customers in the city of Yogyakarta (t count = 3.560; significance value 0.000